High-Performance Layered Oxides for Sodium-Ion Batteries Achieved through Combined Aluminum Substitution and Surface Treatment - Mariya Kalapsazova; Rositsa Kukeva; Sonya Harizanova; Pavel Markov; Diana Nihtianova; Ekaterina Zhecheva; Radostina Stoyanova (Batteries, 2023)
Layered sodium transition metal oxides belong to electrode materials for sodium-ion batteries that combine, in a better way, high performance with environmental requirements. However, their cycling stability is still far from desirable. Herein, we demonstrate a rational approach to control the cycling stability of sodium-deficient nickel manganese oxides, Na2/3Ni1/2Mn1/2O2, with two- and three-layer stacking through Al substitution and Al2O3 treatment. Layered Na2/3Ni1/2Mn1/2O2 oxide displays a limited ability to accommodate aluminum in its structure (i.e., up to 8 at. %). The substitution of Ni ions with electrochemically inactive Al3+ ions and keeping the amount of Mn ions in Na2/3Ni1/2−xAlxMn1/2O2 leads to the stabilization of the two-layer stacking and favors the participation of lattice oxygen in the electrochemical reaction in addition to Ni ions. This results in an increase in the specific capacity of the Al-substituted oxides. Furthermore, the kinetics of the cationic migration between layers occurring during oxide cycling was manipulated by oxide morphology. The best cycling stability is observed for Na2/3Ni0.42Al0.08Mn1/2O2 having a column-like morphology of stacked plate-like particles along the common faces. The treatment of the layered oxides with Al2O3 mitigates the Mn dissolution reaction during electrode cycling in the NaPF6-based electrolyte, thus contributing to a high cycling stability.